Bi‐allelic mutations of CCDC88C are a rare cause of severe congenital hydrocephalus. Issue 3 (17th January 2018) - Ruggeri, Gaia; Timms, Andrew E.; Cheng, Chi; Weiss, Avery; Kollros, Peter; Chapman, Teresa; Tully, Hannah; Mirzaa, Ghayda M.
Abstract : Congenital or infantile hydrocephalus is caused by genetic and non‐genetic factors and is highly heterogeneous in etiology. In recent studies, a limited number of genetic causes of hydrocephalus have been identified. To date, recessive mutations in the CCDC88C gene have been identified as a cause of non‐syndromic congenital hydrocephalus in three reported families. Here, we report the fourth known family with two affected individuals with congenital hydrocephalus due to a homozygous mutation in the CCDC88C gene identified by whole exome sequencing. Our two newly described children, as well as the previously published ones, all shared several features including severe infantile‐onset hydrocephalus, mild to severe intellectual delay, varying degrees of motor delay, and infantile onset seizures. All identified homozygous mutations in CCDC88C abolish the PDZ binding site necessary for proper CCDC88C protein function in the Wnt signaling pathway. Our report further establishes CCDC88C as one of the few known recessive causes of severe prenatal‐onset hydrocephalus. Recognition of this syndrome has important diagnostic and genetic implications for families identified in the future.